Significance of standard and speckle-tracking echocardiography for early diagnosis of asymptomatic left ventricular dysfunction in type 2 diabetes - T. G. Utina; D. U. Akasheva; D. V. Korsunsky; O. M. Drapkina (Кардиоваскулярная терапия и профилактика, 2023)
Aim. To study the relationship between echocardiographic parameters of left ventricular (LV) function and carbohydrate metabolism indicators, as well as to evaluate value of speckle-tracking echocardiography (STE) in the early diagnosis of subclinical LV dysfunction in type 2 diabetes (T2D) in individuals without clinical manifestations of cardiovascular disease (CVD).Material and methods. The study included 120 people of both sexes aged 45 to 75 years. Patients were divided into three following groups: 1 — with T2D (n=53), 2 — with prediabetes (n=20), 3 — control, without carbohydrate metabolism disorders (n=47). All participants underwent transthoracic two-dimensional echocardiography with an assessment of standard systolic and diastolic parameters, as well as quantitative STE indicators. In addition, all participants underwent laboratory diagnostics of carbohydrate metabolism disorders, which included the determination of blood fasting glucose, glycated hemoglobin (HbA1c), insulin, and C-peptide, as well as insulin resistance index estimation.Results. In patients with T2D, in comparison with the control group, diastolic function parameters were significantly different as follows: a lower value of early to late diastolic transmitral flow velocity (E/A) ratio, the ratio of early transmitral flow velocity to early diastolic mitral annulus velocity (E/e'), mitral annular velocity (e') and higher isovolumic relaxation time (IVRT), as well as early diastolic flow deceleration time (DT). According to multivariate analysis, not only T2D, but also prediabetes was an independent predictor of diastolic dysfunction. The Simpson's LV ejection fraction was preserved in all study participants. In patients with T2D, in comparison with the control, according to STE, a decrease in global longitudinal strain (GLS), an increase in apical rotation, and also LV twist were revealed. In a multivariate regression analysis, the HbA1c level had an inverse relationship with GLS and was an independent predictor of its decrease, and the T2D duration was a significant predictor of twisting changes, apical and basal rotation. At the same time, GLS and LV twist had a high sensitivity in determining the decrease in E/A, e'/a', e', as well as the increase in IVRT.Conclusion. In patients with T2D without CVD manifestations, sub-clinical signs of diastolic dysfunction were revealed, such as delayed LV relaxation; systolic dysfunction with preserved ejection fraction was manifested by a decrease in GLS, as well as an increase in apical rotation and LV twisting, identified by STE. The severity of asymptomatic LV systolic-diastolic dysfunction was associated with the severity of glucose metabolism disorders and T2D duration.